2013
DOI: 10.1371/journal.pone.0073942
|View full text |Cite|
|
Sign up to set email alerts
|

Concomitant Targeting of Multiple Key Transcription Factors Effectively Disrupts Cancer Stem Cells Enriched in Side Population of Human Pancreatic Cancer Cells

Abstract: BackgroundA major challenge in the treatment of pancreatic ductal adenocarcinoma is the failure of chemotherapy, which is likely due to the presence of the cancer stem cells (CSCs).ObjectiveTo identify side population (SP) cells and characterize s-like properties in human pancreatic cancer cell lines (h-PCCLs) and to exploit the efficacy of concomitant targeting of multiple key transcription factors governing the stemness of pancreatic CSCs in suppressing CSC-like phenotypes.MethodsFlow cytometry and Hoechst 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…ABCG2 is a member of the ATP binding cassette (ABC) transporters in sub-family G, isoform 2. This protein is responsible for transporting molecules across cellular membranes and is found in stem cell populations from pancreas (Wang et al, 2013), cornea (Stasi et al, 2014), and in lung cancer (Niu et al, 2013). Nestin is a type IV intermediate filament while Musashi 1 is a neural RNA-binding protein that regulates expression of target mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…ABCG2 is a member of the ATP binding cassette (ABC) transporters in sub-family G, isoform 2. This protein is responsible for transporting molecules across cellular membranes and is found in stem cell populations from pancreas (Wang et al, 2013), cornea (Stasi et al, 2014), and in lung cancer (Niu et al, 2013). Nestin is a type IV intermediate filament while Musashi 1 is a neural RNA-binding protein that regulates expression of target mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al, 2013;Zhou et al, 2008), we observed SP cells in the control Panc-1 cells by the SP assay. Wang et al, 2013;Zhou et al, 2008), we observed SP cells in the control Panc-1 cells by the SP assay.…”
mentioning
confidence: 75%
“…Some in vitro studies showed that blocking cis-acting elements, that are common for pluripotency maintaining Transcription Factor SOX-2 (Sox2), Oct4, and proto-Oncogene C-Myc (cMyc), dramatically decreased CSCs proliferation and their ability to generate tumors in nude mice [15]. Equally, simultaneous knockdown of OCT4 and its target Nanog led to decreased proliferation, migration, invasiveness and tumorigenesis of putative pancreatic cancer stem cells [129].…”
Section: Cscs As Therapeutic Targetsmentioning
confidence: 99%
“…Along with CD133, aldehyde dehydrogenase 1 (ALDH1) is also considered a useful marker of stemness, both of which are currently being used for flow cytometry sorting of stem-enriched side populations [15]. Increased activity of ALDH1 was associated with CSCs and has been correlated with invasion, migration and poor overall survival in patients with pancreatic cancer [16].…”
Section: Introductionmentioning
confidence: 99%